LITERATURE STUDY: THE RELATIONSHIP BETWEEN GREEN HRM, CORPORATE REPUTATION, AND EMPLOYEE WELL-BEING - Naryanto, Naryanto; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This paper examines the relationship between Green Human Resource Management (GHRM), corporate reputation, and employee well-being through a comprehensive literature review. GHRM is an approach that integrates environmentally friendly practices into human resource management, increasingly important in the context of global sustainability. The aim of this study is to analyze existing literature and identify how the implementation of GHRM can influence corporate reputation and employee well-being. The analysis results show that the application of GHRM contributes to enhancing corporate reputation, which in turn positively impacts employee well-being. By creating a healthier work environment and promoting employee engagement in sustainability practices, GHRM not only improves the company's image but also increases employee satisfaction and motivation. These findings highlight the importance of integrating GHRM into human resource management strategies to achieve sustainable and beneficial outcomes for both companies and employees